International Standard Classification of Occupations survey report: Implications for the World Federation of Occupational Therapists. Issue 2 (3rd July 2017) - ,; von Zweck, C.; Klaiman, D.; Pattison, M.
ABSTRACT: The International Standard Classification of Occupations (ISCO) provides a framework for international reporting of data on occupations, as well as serves as a model for the development of more specific national/regional occupational classifications. Occupational therapists are not uniquely described in the ISCO, restricting data collection and exchange regarding the profession. Results of an online survey of member organisations of the World Federation of Occupational Therapists indicated a low awareness of issues relating to the occupational classification of the profession. However, findings that over two-thirds of countries with a national/regional occupational classification include a specific category naming occupational therapists provide evidence of the need for this type of categorisation. Given the important implications of this issue for the development of the profession, international lobby efforts are necessary to change the categorisation of occupational therapists in the ISCO.